1977
DOI: 10.1210/jcem-44-5-902
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Protein in Mid-Term Human Amniotic Fluid which Reacts in the Somatomedin-C Radioreceptor Assay*

Abstract: Amniotic fluid contains materials other than insulin which react in a somatomedin C radioreceptor assay using human placental membranes. The material in mid-gestational amniotic fluid which reacted with the somatomedin C radioreceptor assay eluted slightly after albumin from a Sephadex G-150 column equilibrated with 0.1M NH4HCO3. Neither boiling nor treatment of this fraction with 1% formic acid yielded small molecular weight somatomedin-like peptides. Separation of the somatomedin reactive material (Sm RM) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
1

Year Published

1981
1981
1999
1999

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(38 citation statements)
references
References 13 publications
2
35
0
1
Order By: Relevance
“…It has been suggested that IGFs stimulate follicular growth, dif ferentiation and steroidogenesis. IGF-1 has been reported to stimulate aromatase mRNA levels and P450arom activi ty in cultured human granulosa-luteal cells [20], A family of binding proteins (IGFBP-1-6) which binds with both IGF-I and II with high affinity has been reported to be present in serum [10], amniotic fluid [5,6], other body fluids [7][8][9]11], and in the conditioning medium from several cultured cell lines [21]. It has been suggested that the IGFBPs modulate the availability of the IGF to their target cells, and play an important role in the regulation of autocrine or paracrine action of IGF.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that IGFs stimulate follicular growth, dif ferentiation and steroidogenesis. IGF-1 has been reported to stimulate aromatase mRNA levels and P450arom activi ty in cultured human granulosa-luteal cells [20], A family of binding proteins (IGFBP-1-6) which binds with both IGF-I and II with high affinity has been reported to be present in serum [10], amniotic fluid [5,6], other body fluids [7][8][9]11], and in the conditioning medium from several cultured cell lines [21]. It has been suggested that the IGFBPs modulate the availability of the IGF to their target cells, and play an important role in the regulation of autocrine or paracrine action of IGF.…”
Section: Discussionmentioning
confidence: 99%
“…The first IGF-BP (BP1) was isolated independently by Chochinov et al [121]and Drop et al [122]from amniotic fluid. IGF-BP-1 was later shown by Suikkari et al [123]and others to be regulated directly by insulin, explaining its acute changes with nutrition and its opposite changes with the GH-status.…”
Section: Sulphation Factor-somatomedin Is Insulin-likementioning
confidence: 99%
“…Term placental ILAs (22) and MSA (7) cytosolic binding proteins have previously been characterized, but i t is not known whether the midterm binding activity detected in this study corresponds to these molecules. The high level of ILAs specific binding in midterm cytosol is of interest in view of the increase in IGF binding proteins in midterm amniotic fluid (10,18). Thus our results raise the question of whether the large molecular weight placental cytosol binding proteins (estimated molecular weight 60,000 daltons) subserve a precursor function for the smaller IGF binding proteins (estimated molecular weight 34,500 daltons) in amniotic fluid.…”
Section: Discussionmentioning
confidence: 68%